Efficacy of direct hemoperfusion with a polymyxin B‐immobilized fiber column in miliary tuberculosis. Issue 3 (26th December 2016) - Kawano, Yasumasa; Nagashima, Ryotaro; Morimoto, Shinichi; Izutani, Yoshito; Yamasaki, Reiko; Nishida, Takeshi; Iwaasa, Mitsutoshi; Ishikura, Hiroyasu
Abstract : Case: A 75‐year‐old woman presented with a 10‐day history of intermittent fever, general fatigue, and progressive dyspnea. Although she had a low PaO2 /FIO2 ratio, the cause of acute respiratory distress syndrome was not clear until day 9 in hospital. Outcome: We treated the patient with direct hemoperfusion with a polymyxin B‐immobilized fiber column incidentally; the PaO2 /FIO2 ratio improved following this therapy. Acid‐fast bacilli, which were not seen in the sputum on admission, were detected in cultures from sputum, urine, bone marrow, liver biopsy, and blood samples, with a real‐time polymerase chain reaction assay confirming tuberculosis. She was immediately transferred to a specialized tuberculosis hospital, and after a 3‐month treatment, was discharged. Conclusion: Treatment with polymyxin B‐immobilized fiber column may provide good results for pulmonary oxygenation in acute respiratory distress syndrome caused by tuberculosis. Abstract : Clinical course of the PaO2 /FiO2 ratio, C‐reactive protein (CRP) levels, neutrophil count, treatment, and ventilator settings of a 75‐year‐old woman with acute respiratory distress syndrome due to tuberculosis. Direct hemoperfusion with a polymyxin B‐immobilized fiber column likely initiated fast improvement of the PaO2 /FiO2 ratio before initiation of antituberculosis therapy. PEEP, positive end expiratory pressure.